Study on heart rate recovery index to predict maximum oxygen uptake in healthy adults aged 30 to 60 years old - Miao, Guoqing; Yan, Qi; Zhu, Houyuan; Li, Fantai (Frontiers in Physiology, 2024)
ObjectiveTo explore the feasibility of post-exercise heart rate recovery indicators for predicting maximum oxygen uptake (VO2max) in healthy adults aged 30–60 years.Methods260 healthy adults who did not perform regular exercise were randomly recruited and divided into a model group (n = 200) and a verification group (n = 60). Measure body fat percentage, weight, height and other indicators, and complete a cardiopulmonary exercise test as required to measure VO2max and heart rate recovery (HRR1, HRR2) in the first and second minutes after exercise. Equations are established through stepwise regression method, and the selected optimal equation is tested for back substitution.ResultsThe optimal equation is: Absolute VO2⁡max=−0.528+0.039*weight−3.463*body fat rate+0.042*HRR2−0.180*gender male=1,female=2. Analysis of variance, goodness-of-fit test, VIF test, Shapiro-Wilk test, and Durbin-Watson test indicate that the equation is more reliable; Pearson product-moment correlation analysis, paired t test, and Bland-Altman consistency test indicate that the equation is more valid good.ConclusionThe regression equation established through heart rate recovery after exercise can be used to predict VO2max in healthy adults aged 30–60 years.